Alterations of gut fungal microbiota in patients with rheumatoid arthritis - Sun, Xiaoyu; Wang, Yushuang; Li, Xinke; Wang, Meiling; Dong, Jianyi; Tang, Wei; Lei, Zengjie; Guo, Yuling; Li, Ming; Li, Yuyuan (PeerJ, 2022)
Background Rheumatoid arthritis (RA) is a systemic autoimmune disease, in addition, gut microbiota plays an important role in the etiology of RA. However, our understanding of alterations to the gut fungal microbiota in Chinese population with RA is still limited. Methods Serum samples were obtained from 62 patients with RA, and 39 age- and gender-matched healthy controls (HCs). Fecal samples were obtained from 42 RA patients and 39 HCs. Fecal fungal microbiota targeting internal transcribed spacer region 2 (ITS2) rRNA genes was investigated using MiSeq sequencing, as well as their associations with some diagnostic biomarkers for RA. Results Our results showed that the fungal diversity did not alter in RA patients but taxonomic composition of the fecal fungal microbiota did. The gut mycobiota of RA patients was characterized by decreased abundance of Pholiota, Scedosporium, and Trichosporon. The linear discriminant analysis (LDA) effect size analysis (LEfSe) analysis identified several RA-enriched fungal genera, which were positively correlated with most RA biomarkers. Furthermore, since RA is an age- and gende-related disease, we classified RA patients into subgroups with age and gender and analyzed the sequencing results. Our data demonstrated that Wallemia and Irpex were the most discriminatory against RA patients over 60 years old, while Pseudeurotiaceae was the most discriminatory against female RA patients. Conclusions The case-control study presented here confirmed the alterations of gut fungal microbiota in Chinese patients with RA, and we speculated that the fungal dysbiosis may contribute to RA development.
Keywords: Rheumatoid arthritis; Dysbiosis; Gut mycobiota; Age; Gender